A handbook for agrohydrology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Handbook for agrohydrology by S Miller 1994 143pp price UKL30.00 ISBN 0 85954 389